Animal kingdom. The sixth and final season [videorecording (DVD)] - Hatosy, Shawn, 1975-; Robson, Ben; Weary, Jake, 1990-; Cole, Finn, 1995- (Warner Bros. Entertainment Inc., 2022)
In the sixth and final season, the Cody boys discover that they can't outrun their past. With their empire expanding, a cold case investigation sets off a series of events that puts the entire family in jeopardy. Revenge, betrayal, and a reckoning with long-forgotten violence leads to an explosive conclusion six seasons in the making.